MAGISME ISLAM SASAK: FUNGSIONALISASI MANTRA QUR’ANISEBAGAI SOLUSI PROBLEMATIKA KEHIDUPAN MASYARAKAT PEDESAAN DI LOMBOK - Lestari Lestari; Ervina Titi Jayanti (Potret Pemikiran, 2020)
ABSTRACTThe Sasak ethnic group in Lombok, West Nusa Tenggara, are fanatical adherents of Islam, especially rural communities. They believe in, understand and practice Islam based on the ideology of the Sufism which is synonymous with strong belief in mystical problems and spells in solving life problems faced. The Qur'an for rural Muslims, the Sasak ethnic group, is believed to be a magical tool in the form of a spell which if it can function as a solution to the problems of life. This study aims to reveal the factors that cause the birth of the practice of using Qur'anic spells and the forms of practice of using Qur'anic spells. This research is a field research related to socio-cultural problems. The approach used is religious anthropology and historical approaches. Methods of data collection are done by means of observation, interviews and documentation studies. The results showed that rural Muslims of the Sasak ethnic group adhere to the ideology of the sufism which is identical with a high belief in the benefits of the Qur’anic spell as a solution to life problems experienced, such as functioning as a treatment for diseases that are medical and non-medical in nature, to protect themselves or as a means of supernatural powers. As a way for the sake of getting a mate, used to get offspring, and as a means of house keeping.Keywords: Magism; Qur’anic spell, Sasak ethnicABSTRAKEtnis Sasak di Lombok Nusa Tengga Barat tergolong penganut agama Islam yang fanatik, terutama masyarakat pedesaan. Mereka meyakini, memahamai dan mengamalkan Islam berdasarkan faham tarekat yang identik dengan keyakinan yang kuat pada masalah mistik dan mantra dalam menyelesaikan problematika kehidupan yang dihadapi. Al-Qur’an bagi Muslim pedesaan etnis Sasak diyakini sebagai alat magis dalam bentuk mantra yang jika bisa berfungsi sebagai solusi bagi problematika kehidupan.Penelitian ini bertujuan untuk mengungkap faktor-faktor penyebab lahirnya praktik penggunaan mantra Alquran dan bentuk-bentuk praktik penggunaan mantra Alquran. Penelitian ini merupakan penelitian lapangan yang berkaitan dengan masalah sosial budaya. Pendekatan yang digunakan adalah antropologi Agama dan pendekatan sejarah. Metode pengumpulan data dilakukan dengan cara observasi, wawancara dan studi dokumentasi. Hasil penelitian menunjukkan bahwa muslim pedesaan etnis Sasak menganut faham tarekat yang identik dengan kepercayaan yang tinggi pada manpaat mantra Quranisebagai solusi bagi problematika kehidupan yang dialami, seperti berfungsi sebagai pengobatan penyakit yang bersifat medis dan non medis, untuk melindungi diri atau alat kesaktian, untuk dijadikan sebagai pelet demi mendapatkan jodoh, dipergunakan untuk mendapatkan keturunan, dan sebagai alat penjaga rumah.Kata Kunci: Magisme; MantraQur’ani; EtnisSasak